1994
DOI: 10.1128/mcb.14.3.1939
|View full text |Cite
|
Sign up to set email alerts
|

The bZIP transactivator of Epstein-Barr virus, BZLF1, functionally and physically interacts with the p65 subunit of NF-kappa B.

Abstract: The Epstein-Barr virus (EBV) BZLF1 (Z) immediate-early transactivator initiates the switch between latent and productive infection in B cells. The Z protein, which has homology to the basic leucine zipper protein c-Fos, transactivates the promoters of several replicative cycle proteins. Transactivation efficiency of the EBV BMRF1promoter by Z is cell type dependent. In B cells, in which EBV typically exists in a latent form, Z activates the BMRF1 promoter inefficiently. We have discovered that the p65 componen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
75
0
1

Year Published

1995
1995
2021
2021

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 115 publications
(79 citation statements)
references
References 74 publications
3
75
0
1
Order By: Relevance
“…Equal amounts of proteins were incubated with 2 ,u of either a hRARa-specific monoclonal antibody (RalO) (Dianova, Hamburg, Germany) or an unrelated anti-Gal4-specific antibody (Santa Cruz Biotechnology) for 4 h at 4°C. Protein complexes were precipitated with 10 ,ul of protein G-Sepharose (Pharmacia) for 1 h at 4°C, washed, and analyzed as described (18).…”
Section: Methodsmentioning
confidence: 99%
“…Equal amounts of proteins were incubated with 2 ,u of either a hRARa-specific monoclonal antibody (RalO) (Dianova, Hamburg, Germany) or an unrelated anti-Gal4-specific antibody (Santa Cruz Biotechnology) for 4 h at 4°C. Protein complexes were precipitated with 10 ,ul of protein G-Sepharose (Pharmacia) for 1 h at 4°C, washed, and analyzed as described (18).…”
Section: Methodsmentioning
confidence: 99%
“…Generally, the regulation of cellular genes by Zta is at the RNA level. It has been demonstrated that Zta modulates the expression of the p65 subunit of NFκB, 67 transforming growth factor β (TGFβ) and Retinolmetabolizing Enzyme, DHRS9, 68 through directly binding to their promoter sequences. Zta can also interact with some cellular proteins, including the retinoic acid receptors RAR and RXR, 69 the TATA binding protein TFIID, 70 the C/EBP transcription factor 40 and tumor suppressor p53.…”
Section: Characterization Of Ztamentioning
confidence: 99%
“…It is reported that bZIP-containing proteins such as Fos, Jun, and BZLF interact with p65 through the bZIP domain. [13][14][15] Based on the fact that ICER also contains bZIP domain, we tested whether ICER associates with p65. Indeed, we recovered all four isoforms of HA-tagged ICER via immunoprecipitation (IP) with Flag-tagged p65 (Figure 3a).…”
Section: Icer Deficiency Promotes P65 Dna-binding and Inflammatory Rementioning
confidence: 99%